Phytochemical Modulation of Neurotransmitter Systems and Neuroplasticity in Depression and Anxiety: A Mechanistic Review - Rini, Tri Diana Puspita; Savinatunnajah, Savinatunnajah; Yustina, Eka Rosa; Ramadhany, Gisela Amaliah Putri; Shafara, Putri Aprillia; Rahma, Oliffia (Sciences of Pharmacy, 2025)
Depression and anxiety are among the most prevalent mental health disorders worldwide, contributing substantially to disability and mortality, particularly among young adults aged 15–24 years. Their pathophysiology is closely associated with dysregulation of key neurotransmitters, emphasizing the need for safer and more effective long-term therapeutic strategies. Herbal medicine represents a promising alternative due to its multifaceted bioactivity and lower incidence of adverse effects. This review systematically evaluates bioactive compounds from selected medicinal plants and their modulatory effects on neurotransmitter pathways involved in depression and anxiety. Relevant studies published within the past five years were retrieved from PubMed, Scopus, and ScienceDirect databases, with inclusion criteria encompassing in vitro and in vivo investigations of phytochemical actions on neurotransmitter systems. The analysis revealed that plants such as Melissa officinalis (lemon balm), Mimosa pudica, Senna alexandrina, Helianthus annuus, Rosa spp., Laurus nobilis, Mentha piperita, Citrus reticulata, Centella asiatica, Chamaemelum nobile, and Ginkgo biloba exhibit significant antidepressant and anxiolytic properties through modulation of monoaminergic transmission, regulation of the hypothalamic–pituitary–adrenal (HPA) axis, and enhancement of neuroplasticity. These plants also demonstrate antioxidant, anti-inflammatory, and neuroprotective activities that further support their therapeutic potential. In conclusion, herbal-based interventions may serve as valuable complementary approaches for managing depression and anxiety. Nevertheless, well-designed clinical studies are essential to validate their efficacy, safety, and mechanisms in long-term use.